Integration of TPACK and Education for Sustainable Development in Digital Green Chemistry Worksheets: Efforts to Enhance Student Creativity through Contextual Learning - Siti Herlina Dewi; Vinna Lavenia; Agung Tri Prasetya; Eko Budi Susatyo; Sri Haryani; Sri Wardani (Universitas Sebelas Maret, 2025)
This research investigates the development and effectiveness of a digitally delivered worksheet designed to enhance students’ creative thinking in green chemistry through the integration of Technological Pedagogical Content Knowledge (TPACK) and Education for Sustainable Development (ESD). Grounded in both constructivist learning theory and the framework of sustainability education, the study utilizes digital technology to facilitate contextual learning by engaging students in a real-world project: transforming used cooking oil into aromatherapy candles. The worksheet was implemented in a quasi-experimental one-group pretest-posttest design involving 34 tenth-grade students. A two-tiered test was used to assess the impact on creative thinking, measuring four indicators: fluency, flexibility, originality, and elaboration. Statistical analyses demonstrated significant improvement across all indicators, with flexibility showing the highest normalized gain (N-Gain = 0.72) and a large effect size (Cohen’s d = 1.24). These outcomes align with prior studies emphasizing TPACK’s capacity to foster higher-order thinking skills and ESD’s role in improving sustainability literacy. The findings underscore the promise of TPACK-ESD-integrated digital resources as effective tools for cultivating creativity and sustainability-oriented competencies in chemistry education. This study also highlights broader implications for curriculum reform, teacher professional development, and the institutional adoption of digital, sustainability-focused learning materials.